ANALISIS SIKLUS PENGELUARAN PADA CV. PURWA DAYA SEJAHTERA PALEMBANG - Rizal Effendi; Lili Syafitri (Jurnal RATRI (Riset Akuntansi Tridinanti), 2020)
ABSTRACK               The expenditure cycle is also used by companies to maintain good relations with suppliers, because low prices and good quality alone do not guarantee the smooth running of the company, but also require good relations with suppliers. With good relationships, companies can buy goods with more confidence in their quality and with more confidence in the adequacy of the goods the company needs. Without good relations, the company may get low prices and relatively good goods, but it may not be guaranteed when the goods will be in stock.            The accounting information system has three basic functions in the expenditure cycle, namely obtaining and processing data on various business activities, storing and managing data to support decision making, and providing control functions to ensure data reliability and safeguarding Company resources. Keywords : accounting information system, expenditure cycle